Tissue Engineering: bioethics and bioartificial constructs - Donati, Luigi; Tallacchini, Mariachiara (Medicina e Morale, 1997)
Tissue engineering refers to an interdisciplinary field in which the principles of engineering and the life sciences are applied for the understanding of structure/function relations in normal and pathological tissues and toward the generation of biological substitutes aimed at the creation, preservation, or restoration of lost tissue or organ function. This recent domain of research and clinical applications, whose outputs until now consist namely of artificial skin, cartilage and bone, could represent in the future a major alternative to the transplant of human organs. Tissue engineering also brings up bioethical questions. Some ethical issues related to tissue engineering are well known problems, which are shared by many biomedical technologies. Some other problems, however, are for the first time raised by tissue engineering. How to regulate tissue donation is a typical bioethical theme; the relation between market and scientific research has been discussed yet not well-explored; on the contrary, the status of tissue-engineered constructs poses a completely new challenge to bioethical thought. Bioartificial entities belong to a peculiar ontological set, halfway between the natural and the artificial realm: in fact, they are frequently composed of human tissues, but at the same time, because of the technical transformation to which they are submitted, they seem industry artifacts. Law - particular patent law - plays an interesting role in redefining the distinction between natural and artificial. Law integrates scientific definitions of scientific products, and becomes consequently highly relevant to the bioethical assessments. Due to the novelty of this subject, this paper is essentially a reviewing work of the more important achievements of tissue engineering and the main ethical topics related to it.